2020
DOI: 10.1007/s42729-020-00195-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Marine Algae Extracts in Water Stress Resistance of Onion Under Semiarid Conditions

Abstract: Availability of water for food production is a global concern; thus, increasing water productivity has been become a necessary. Deficit irrigation is a good strategy to increase water use efficiency, but it may affect negatively on plant physiology and crop productivity. Little is known about the effect of marine algae extracts on water stress resistance and yield of onion grown on semiarid regions. Therefore, field experiments were conducted in 2018 and 2019 growing seasons to study the effect of foliar appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
5
16
0
1
Order By: Relevance
“…These findings show that the plants primed with seaweed extracts were subjected to less stress than the control plants, resulting in healthy growth. The results of the current study are consistent with those of Almaroai and Eissa (2020) and Campobenedetto et al (2021). The fact that most of the plant's energy is directed to the biosynthetic route of macromolecules like carbohydrates and proteins may explain the lower proline accumulation in wheat seedlings.…”
Section: Discussionsupporting
confidence: 89%
“…These findings show that the plants primed with seaweed extracts were subjected to less stress than the control plants, resulting in healthy growth. The results of the current study are consistent with those of Almaroai and Eissa (2020) and Campobenedetto et al (2021). The fact that most of the plant's energy is directed to the biosynthetic route of macromolecules like carbohydrates and proteins may explain the lower proline accumulation in wheat seedlings.…”
Section: Discussionsupporting
confidence: 89%
“…Our results determined at seedling and elongation stages showed that spraying SEs could significantly increase the SPAD value of sugarcane leaves, which indicated that the application of SEs increased chlorophyll content in leaves (Figure 2), which is also supported by other reports (Lingakumar et al, 2004;Ali et al, 2016Ali et al, , 2019. This might be due to the existence of betaine, amino acids, and other active substances in SEs that inhibit the degradation of chlorophyll (Blunden et al, 1996), Seaweed extracts also contain magnesium, which is necessary for chlorophyll synthesis (Almaroai and Eissa, 2020).…”
Section: Effects Of Ses On Sugarcane Growth and Cane Yieldsupporting
confidence: 84%
“…Our results determined at seedling and elongation stages showed that spraying SEs could significantly increase the SPAD value of sugarcane leaves, which indicated that the application of SEs increased chlorophyll content in leaves ( Figure 2 ), which is also supported by other reports ( Lingakumar et al, 2004 ; Ali et al, 2016 , 2019 ). This might be due to the existence of betaine, amino acids, and other active substances in SEs that inhibit the degradation of chlorophyll ( Blunden et al, 1996 ), Seaweed extracts also contain magnesium, which is necessary for chlorophyll synthesis ( Almaroai and Eissa, 2020 ). Our results showed that spraying SEs had a significant effect on the photosynthetic rate of sugarcane leaves which were consistent with those of SPAD, and these resulted in a stronger ability of plants to maintain a better photosynthetic performance ( Santaniello et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the application of seaweed extract was beneficial to crop growth and development. The researchers reported that spraying seaweed extract had positive impacts on the accumulation of mineral elements and photosynthesis pigments [ 17 ]. Foliar spraying seaweed extract on onion reportedly increased the absorption of N, P, and K by 116, 113, and 93% in comparison with the control plants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%